2009
DOI: 10.1007/s00268-009-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Total Pelvic Exenteration for Primary and Recurrent Malignancies

Abstract: Introduction Complete resection is the most important prognostic factor in surgery for pelvic tumors. In locally advanced and recurrent pelvic malignancies, radical margins are sometimes difficult to obtain because of close relation to or growth in adjacent organs/structures. Total pelvic exenteration (TPE) is an exenterative operation for these advanced tumors and involves en bloc resection of the rectum, bladder, and internal genital organs (prostate/ seminal vesicles or uterus, ovaries and/or vagina). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
89
3
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 49 publications
11
89
3
16
Order By: Relevance
“…Recurrence in rectal carcinoma is scarcely tolerable for patients because there is a higher risk of permanent stoma that may lead to pelvic exenteration and increased morbidity in patients because of deep pelvic abscess, delay in perineum healing and leakage (Wiig et al, 2007;Ferenschild et al, 2009). Andreoni et al (2007) showed that recurrence in rectal cancer is significantly higher than with colon cancer (14% versus 6.1%; p<000.1).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence in rectal carcinoma is scarcely tolerable for patients because there is a higher risk of permanent stoma that may lead to pelvic exenteration and increased morbidity in patients because of deep pelvic abscess, delay in perineum healing and leakage (Wiig et al, 2007;Ferenschild et al, 2009). Andreoni et al (2007) showed that recurrence in rectal cancer is significantly higher than with colon cancer (14% versus 6.1%; p<000.1).…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates at 5 years for primary advanced rectal malignancy, recurrent rectal tumours and tumors of the uterine cervix were 66%, 8% and 45%, respectivley. 11 Wydra et al reported a mortality rate of 7%, of which intraoperative mortality accounted for 3.5%. 12 Major postoperative complications include bleeding, infection, wound dehiscence, and anastomotic leak in the intestines, urinary pouch or ureteral sites.…”
Section: Discussionmentioning
confidence: 99%
“…конти-нентный гетеротопический резервуар из слепой киш-ки с умбиликостомой -3 (3,3 %), W-образная илео-цистопластика по Hautmann -8 (8,7 %), операция Bricker -58 (63,0 %); ректосигмопластика Mainz pouch чеиспускательного канала), задняя экзентерация -ор-ганов задней части полости малого таза (репродуктив-ных органов и нижних отделов кишечника), а тотальная экзентерация включает одновременное выполнение передней и задней экзентерации. Данная операция, особенно тотальная экзентерация, ассоциирована со значительной частотой осложнений, высокой ле-тальностью и снижением качества жизни пациенток [6,7]. Поэтому для оптимизации результатов тазовой эк-зентерации важнейшее значение имеет всесторонняя оценка различных аспектов ее применения, что и опре-деляет актуальность настоящего исследования.…”
Section: диагностика и лечение опухолей мочеполовой системы рак мочеunclassified